KEPASTIAN HUKUM TERHADAP PEMBENTUKAN DAN OPTIMALISASI UNIT PENGUMPULAN ZAKAT (UPZ) SERTA PEMOTONGAN ZAKAT, INFAK DAN SHAODAQAH DI KABUPATEN BANYUASIN - Iswahyudi, Iswahyudi; Kencana, Ulya (Program Studi Muamalah Fakultas Syariah dan Hukum, 2019)
Banyuasin Regency is an area that has a fairly dense population that is predominantly Muslim, abundant natural products and its territory is quite extensive. So that it has a large potential for zakat which must be managed well and must have regulations that have legal certainty. The Banyuasin District Government together with the National Amil Zakat Agency (BAZNAS) of the Banyuasin Regency to realize community welfare and carry out the mandate of Law Number 23 of 2011 concerning Management of Zakat, continues to carry out its duties to the maximum extent, including forming and optimizing the Zakat Collecting Unit (UPZ) and Cutting Zakat, Infak and Shodaqah in Banyuasin District. The main issues that are the focus of this thesis research are the legal position, juridical analysis of the contents of the dictum and implementation of the contents of the dictum of the Banyuasin Regent Circular Letter Number: 221 / SE / BAZNAS / 2017 concerning the Formation and Optimization of Zakat Collecting Units (UPZ) and Cutting Zakat, Infak and Shodaqah in Banyuasin Regency.